2019
DOI: 10.7759/cureus.4560
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Apneas Versus Hypopneas: Is There Really a Difference?

Abstract: Introduction Obstructive sleep apnea is diagnosed by identifying obstructive apneas and hypopneas, but no study has shown that it is necessary to distinguish these events from each other. Our goal was to analyze results from polysomnograms to determine if adverse health outcomes were more likely in patients with higher apnea indices relative to their hypopnea indices. Our hypothesis was that scoring apneas separately from hypopneas has no predictive value. Methods A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Odor perception is directly linked to the amount of air entering the nostrils 52 and thus we hypothesized that olfactory stimulation will have a greater influence on hypopnea events in comparison to apnea events. A non-parametric repeated measures ANOVA (Friedman test) with conditions of ‘Stimulation (Odor/Control), and ‘Index’ (Apnea Index/Hypopnea Index) uncovered a main effect of ‘Stimulation’ in which ‘Odor’ nights were associated with lower AI and HI indices, (F = 3.56, Kendall’s W = −18.65, p = 0.021), and a main effect of ‘Index’ in which hypopneas were more frequent than apneas (F = 6.7, Kendall’s W = −20.78, p < 0.001), in line with previous findings 53 . However, in contrast to our hypothesis there was no interaction between ‘Stimulation’ and ‘Index’ (computed on the difference between (Odor - Control) per index, non-parametric test: z =-0.052, p = 0.85, BF 10 = 2.49).…”
Section: Resultssupporting
confidence: 91%
“…Odor perception is directly linked to the amount of air entering the nostrils 52 and thus we hypothesized that olfactory stimulation will have a greater influence on hypopnea events in comparison to apnea events. A non-parametric repeated measures ANOVA (Friedman test) with conditions of ‘Stimulation (Odor/Control), and ‘Index’ (Apnea Index/Hypopnea Index) uncovered a main effect of ‘Stimulation’ in which ‘Odor’ nights were associated with lower AI and HI indices, (F = 3.56, Kendall’s W = −18.65, p = 0.021), and a main effect of ‘Index’ in which hypopneas were more frequent than apneas (F = 6.7, Kendall’s W = −20.78, p < 0.001), in line with previous findings 53 . However, in contrast to our hypothesis there was no interaction between ‘Stimulation’ and ‘Index’ (computed on the difference between (Odor - Control) per index, non-parametric test: z =-0.052, p = 0.85, BF 10 = 2.49).…”
Section: Resultssupporting
confidence: 91%
“…Several factors lead to discrepancies between the reported results: hypopnea definition, AHI threshold, and type of device. Firstly, the hypopnea definition was modified throughout the years and may result in a different number of the total AHI [ 37 , 38 , 39 , 40 , 41 ]. In our review, only three studies used the AASM hypopnea definition (2007, 2016, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Apneas are considered to be a more severe form of obstruction since they feature complete cessation of airflow. However, a recent retrospective review 23 in adult patients with OSA demonstrated that patients with apnea-predominant and hypopneapredominant OSA had similar comorbid medical conditions, including hypertension and cardiovascular disease. Another study 24 failed to demonstrate a difference in clinical outcomes among adult patients with OSA stratified according to apnea vs hypopnea predominance treated with mandibular advancement devices.…”
Section: Discussionmentioning
confidence: 99%